Important cytotoxic and cytostatic effects of new copper(i)–phosphane compounds with N, N, N, O and N, S bidentate ligands. Issue 23 (31st May 2018) - Morais, Tânia S.; Jousseaume, Yann; M. Piedade, M. Fátima; Roma-Rodrigues, Catarina; Fernandes, Alexandra R.; Marques, Fernanda; Villa de Brito, Maria J.; Garcia, M. Helena
Abstract : Synthesis of new phosphane–Cu(i ) complexes with bidentate ligands displaying cytotoxic and cytostatic effects that make them attractive as anticancer agents. Abstract : A family of six phosphane Cu(i ) complexes bearing N, N, N, O and N, S bidentate ligands was synthesized. All the compounds were fully characterized by classical analytical and spectroscopic methods, and five of them were also characterized by X-ray diffraction studies. All the compounds exhibit high cytotoxicity against the human breast cancer cell line MCF7 with IC50 values far lower than those found for cisplatin, a current chemotherapeutic in clinical use. Compounds1̲ and3̲ induce cell cycle arrest in the G2/M phase and cell death by apoptosis. The cytotoxic and cytostatic effects of these compounds on MCF7 cells suggest that they are suitable for further in vivo studies with breast cancer models.